TINJAUAN USHULI TERHADAP PRESEPSI WANITA PEKERJA DALAM MASSA IDDAH AKIBAT CERAI MATI - Huda, Muhammad Hasbulloh; Junaidi, Junaidi (MAQASHID, 2022)
A review of Islamic law on people's perceptions of the implementation of the Iddah of working women, it is explained that the state of emergency does not exceed the level that allows it. In the sense that a working woman is allowed to work fully decorated, that is, only to fulfill the requirements of her job, with the aim that the career woman is not fired or lost her job and if she does not work it can cause starvation for herself and her children. So according to Islamic law, the woman may work and decorate without passing the specified limits.